Evolution of social protection systems: from concepts to modern practice - Яремчук, Сергій; Гнатчук, Оксана; Шестакова, Катерина (Львівський університет бізнесу та права, 2023)
The article examines the peculiarities of social protection development from ancient times to the present. It is established that the initial forms of social protection existed at the level of charity and were not regulated by the state, and the normatively based forms of social protection first appeared in the times of Kievan Rus. The issue of the formation of social insurance as a component of social protection was studied on the example of the Soviet period, since it was at this time that the concept of social security began to take shape at the expense of paid insurance premiums. The author analyzes the trends in the development of social insurance in independent Ukraine and establishes that social insurance reforms in some cases result in narrowing of the constitutional rights of citizens by abolishing certain social services or benefits. A separate assessment is made of the social pension system, which has undergone the greatest transformations and changes over the period of its existence. At the same time, the study shows that the modifications made have not contributed to the main goal of the reforms, since the pension provision of citizens in Ukraine remains low. Additionally, it was found that the types of social protection vary depending on the socio-political and economic situation in the country, which leads to the emergence of temporary forms of social protection. For example, the military-political situation in Ukraine since February 2022 has revealed that new social groups of citizens have emerged that require state protection. In response to public demand, the state has adopted a number of regulations to support citizens affected by the war. Such citizens will need social protection even after the end of the war, but in the global historical dimension, such forms of social protection are not sustainable.
Keywords: Material security, pensions, social protection, social insurance, temporary disability